2020
DOI: 10.34256/ijpefs2027
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Change of Water Polo Rules on the Game Dynamics

Abstract: This research aimed to identify a change in the dynamics of the water polo game related to identifying differences in the number of goals scored before and after the introduction of the current 2019 rules. The sample analyzed 96 matches from the 2018 and 2020 European Water Polo Championships. The sample of variables included five variables for both subsamples, which referred to the total number of goals scored in the match, as well as the total number of goals per quarter. By applying the T-test for small ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Additionally, recent studies found that the change of the direct free-throw line to 6 m away from the goal affected that type of shot frequency [20,21], which was also perceived in the current results, although Serbia tried it more and was efficient. Since in previous research [15] the free throw was the most efficient strategy in even play, the change of its distance does not seem to produce a positive effect.…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…Additionally, recent studies found that the change of the direct free-throw line to 6 m away from the goal affected that type of shot frequency [20,21], which was also perceived in the current results, although Serbia tried it more and was efficient. Since in previous research [15] the free throw was the most efficient strategy in even play, the change of its distance does not seem to produce a positive effect.…”
Section: Discussionsupporting
confidence: 62%
“…The increase in penalties was another effect of the rule changes reported [ 21 ], but, in the current research, they mainly occurred in Croatia’s team. However, results are still in agreement with a study that reported that penalties and power-plays together account for about 56% of goals in elite matches [ 39 ], meaning that more than half of the goals come from disciplinary sanctions for serious fouls.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations